2020
DOI: 10.1371/journal.pone.0239096
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and impact analysis of interdependent characteristics on cascading overload failure of syncretic railway networks

Abstract: To study the performance and mutual influence of a syncretic railway network (SRN) that comprises high-speed railway, regional railway, and urban rail transit under the condition of traffic overload during peak hours, we discuss the interdependent characteristics on cascading overload failure of SRNs under the cooperative organization from the perspective of an interdependent network. However, most existing research on cascading failure in interdependent network ignores the inconsistency between the physical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Hu X et al [ 12 ] found that the high circuity of train paths can be decreased with the construction of a high-speed railway line, which indicates that the structure of the high-speed rail (HSR) network in China should become more complete and that the HSR network can make the Chinese railway network more efficient. Liu S et al [ 13 ] studied the performance and mutual influence of a syncretic railway network (SRN) that comprises high-speed railways, regional railways, and urban rail transit under the condition of traffic overload during peak hours.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hu X et al [ 12 ] found that the high circuity of train paths can be decreased with the construction of a high-speed railway line, which indicates that the structure of the high-speed rail (HSR) network in China should become more complete and that the HSR network can make the Chinese railway network more efficient. Liu S et al [ 13 ] studied the performance and mutual influence of a syncretic railway network (SRN) that comprises high-speed railways, regional railways, and urban rail transit under the condition of traffic overload during peak hours.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fu et al [24] proposed an interdependent cascade model and analyzed the effects of different attack strategies on the robustness of the interdependent network. Liu et al [25] proposed a partially interdependent network model of multimode rail transit, and developed a novel cascading overload failure model with tunable parameters of load redistribution inter subnetwork. Considering the residual capacity, Zhang et al [26] proposed a dynamic load redistribution strategy based on the local load factor of the nodes.…”
Section: Introductionmentioning
confidence: 99%